2020
DOI: 10.24940/theijst/2020/v8/i6/st2006-002
|View full text |Cite
|
Sign up to set email alerts
|

The Model of Rural Youth Empowerment through Red Chili Farming in Sindangkasih Sub-district of Ciamis, Indonesia

Abstract: Decreasing number of farmers for the last ten years tended to obviously massively increase. According to Statistics of Indonesia (Badan Pusat Statistik, BPS), there was annual decline of 1.1 percent during the period 2010-2017. In term of farmer age, it is worrying that most farmers are currently ageing. Result of Agricultural Census (Sensus Pertanian) in 2013 showed that 61.8 percent of farmers were older than 45 years, and it was only 12.2 percent of farmers aged below 35 years. This situation is inline with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on the description above, a research framework is built based on the hypothesis that there are a number of variables that can affect the empowerment of a person or community group. Effendy et al [3] explained the youth involvement to increase the youth empowerment. Meanwhile, [2] Effendy and Sudiro argued about factors that affect the woman empowerment in land use are external factors and farmer group supports.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the description above, a research framework is built based on the hypothesis that there are a number of variables that can affect the empowerment of a person or community group. Effendy et al [3] explained the youth involvement to increase the youth empowerment. Meanwhile, [2] Effendy and Sudiro argued about factors that affect the woman empowerment in land use are external factors and farmer group supports.…”
Section: Methodsmentioning
confidence: 99%
“…This result is in line with [4], [5], [6], who reported that the personal characteristic component is an important indicator in increasing empowerment. In addition, empowerment can also be determined by factors from outside the characteristics, such as a person's involvement in a program or activity [3], also determined by external factors such as; availability of infrastructure, extension activities, farmer group functions, and access to information [7], [8] [9] [10]. Meanwhile, Permana and Effendy [11] explained that the empowerment of women farmer groups is significantly influenced by external factors consisting of; support for group members, the availability of facilities and infrastructure, policy support, and outreach activities.…”
Section: Effect Of Farmer Characteristics On Community Empowermentmentioning
confidence: 99%